Tata Kelola Perusahaan, Financial Leverage, Profitabilitas, dan Pengaruhnya terhadap Praktik Manajemen Laba - Tjhai Fung Jin (Media Bisnis, 2023)
The purpose of this study is to provide empirical evidence regarding the influence of corporate governance, financial leverage, and profitability towards earnings management. The corporate governance consists of managerial ownership, institutional ownership, and board director size. Samples of this research were selected based on the purposive sampling method and resulted in 29 manufacturing companies listed on Indonesian Stock Exchange during the period of 2017-2021 or total 142 data after outlier test. A total of 142 data were analyzed using multiple linear regression. The results of this research show that board director size has significant negative influence on earnings management. The company who has more directors, it shows a good corporate governance and affect on decreasing earnings management pratice. Other variables such as managerial ownership, institutional ownership, financial leverage, and profitability have no influence on earnings management.